THE IMPLICATIONS OF THE COVID-19 PANDEMIC ON MOROCCAN UNIVERSITY STUDENTS - Zamakda Allison, Safwaan (Universitas Nasional, 2021)
The COVID-19 pandemic, first identified in Wuhan, China, was first confirmed to be present in Morocco on the 2nd of March 2020. It swiftly took hold in Moroccan society and spread like wildfire. This led to a surge in deaths, those needing extra and intensive care, and generalised anxiety amongst the population. There was perceived dissatisfaction in how the Moroccan government was handling the crisis, and accordingly, on the 13th of March, schools and universities were closed until further notice. Education was then conducted remotely- on Zoom, Microsoft Teams, WhatsApp, via email and other platforms. This study examines how final-year undergraduate university students felt during this period, and how they felt that the (ongoing) COVID-19 pandemic has affected them, their lives and their studies. This study is important, as the pandemic is ongoing, and despite vaccination efforts, there is the potential for new variants to come into existence and to cause for a recurrence of the issues faced by university students and the wider society to which they belong. It is also in that this area of research is under-researched because the COVID-19 pandemic is ongoing, and that the issues faced by Moroccan university students and general population are tremendously neglected in academic literature, particularly in English-language literature. Therefore, this study examines the concerns, worries, grievances and anxieties of Moroccan final-year undergraduate students, and sheds light on a population sample that is often neglected and forgotten.